Exploring EFL Students’ Writing Strategies in Composing Classroom Action Research (CAR) Proposals - Afdalia, Tiara; Fauzan, Akhmad; Bahing, Bahing (Scripta : English Department Journal, 2024)
This study explored the writing strategies employed by EFL students when composing Classroom Action Research (CAR) proposals, focusing on the frequency of strategy use. Using a quantitative research design, data were collected through a structured questionnaire administered to 48 undergraduate students in the English Language Education Study Program at the University of Palangka Raya. The questionnaire measured the frequency of pre-writing, while-writing, and revising strategies. The findings reveal that students frequently engaged with while-writing strategies, particularly translation from Indonesian to English. The pre-writing stage showed moderate engagement, with students commonly reviewing examples of well-written proposals but less frequently using formal outlining techniques. In the revising stage, feedback from lecturers was highly valued, with students actively using it to improve their proposals. However, self-editing strategies were less emphasized, indicating a reliance on external feedback for revisions. The study concludes that while students benefit from translation and feedback-driven revision, there is a need for more significant support in developing independent revision skills and expanding academic vocabulary.